Electron transport in crossed electric and magnetic fields under the condition of the electron streaming in GaN - Syngayivska, G.I.; Korotyeyev, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
High-field electron transport has been studied in crossed electric and magnetic fields in bulk GaN with doping of 10¹⁶ cm⁻³ and compensation around 90% at the low lattice temperature (30 K). The electron distribution function, the field dependences of the ohmic and Hall components of the drift velocity have been calculated using the Monte Carlo method in the wide range of applied electric (3…15 kV/cm) and magnetic (1…10 T) fields. Two external electrical circuits with short- and open-circuited Hall contacts have been analyzed. For a sample with short-circuited Hall contacts, there are the ranges of magnetic and electric fields where the non-equilibrium electron distribution function has a complicated topological structure in the momentum space with a tendency to formation of the inversion population. For these samples, field dependences of the ohmic and Hall components of the drift velocity have specific character. The ohmic component has the inflection point that corresponds to the maximum point of the Hall component. For the sample with open-circuited Hall contacts, field dependences of the drift velocity demonstrate a sub-linear growth without any critical points. It has been shown that there are ranges of the applied electric and magnetic fields for which the drift velocity exceeds zero magnetic field values